MORAL PROBLEMS IN THE STORIES OF VASILY SHUKSHIN - Chjen E.V.; Ibragimova Dilrabo (Journals Park Publishing, 2022)
The article examines the artistic features of the work of one of the brightest representatives of rural prose in Russian literature: the principles of aesthetics, moral problems and the search for a hero in the stories of V. Shukshin.
Keywords: Moral problems, V. Shukshin's stories, morality, the truth of life, short stories, rustic prose, weirdos.